2021
DOI: 10.1053/j.gastro.2021.08.037
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Cirrhosis: A Combination We Must Strive to Prevent

Feng Su

Abstract: See "Outcomes of SARS-CoV-2 infection in patients with chronic liver disease and cirrhosis: a national COVID cohort collaborative study" by Ge J, Pletcher MJ, Lai JC, N3C Consortium, on page 000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Cirrhotic patients have complex immune disorders and are more susceptible to infection, and the leading causes of mortality are not only respiratory complications but also deterioration of liver function, leading to end-stage liver disease. Patients with cirrhosis are not only at risk of related immune dysfunction, but also are more likely to have comorbidities that predispose them to severe COVID-19, such as diabetes, chronic kidney disease, and heart disease[ 75 ]. However, there is a debate about the risk of cirrhosis on the clinical outcomes of COVID-19.…”
Section: Covid-19-induced Liver Injury In Special Populationsmentioning
confidence: 99%
“…Cirrhotic patients have complex immune disorders and are more susceptible to infection, and the leading causes of mortality are not only respiratory complications but also deterioration of liver function, leading to end-stage liver disease. Patients with cirrhosis are not only at risk of related immune dysfunction, but also are more likely to have comorbidities that predispose them to severe COVID-19, such as diabetes, chronic kidney disease, and heart disease[ 75 ]. However, there is a debate about the risk of cirrhosis on the clinical outcomes of COVID-19.…”
Section: Covid-19-induced Liver Injury In Special Populationsmentioning
confidence: 99%
“…The interaction between SARS-CoV-2 and the liver appears to be a vicious circle, ultimately leading to multiple system organ failure (MSOF) [ 59 ]. Another study showed that COVID-19 was found to increase by 5-fold the chance of death among cirrhotic patients, respectively accounting for a 2.2-fold increase in the death risk of those with decompensated cirrhosis [ 46 , 60 ], but the main cause of death in cirrhotic patients infected with COVID-19 was found to be respiratory failure (71% of the cases in the study), while only 19% of the patients died of complications related to the liver [ 61 ].…”
Section: Covid-19 and Cirrhosismentioning
confidence: 99%
“…Finally, the spectrum of COVID-19related manifestations turned out to be associated with a broad range of systemic symptoms, e.g., neurological and dermatological syndromes, myocardial dysfunction, hyperglycemia, disorders of the gastrointestinal tract and acute kidney failure [9][10][11][12][13][14]. Concomitantly, a lot of observations also started to suggest an existing relationship between SARS-CoV-2 and chronic liver diseases (CLDs), indicating hepatic manifestations of the infection and the exacerbation of existing liver pathologies in the case of COVID-19 [15][16][17][18][19][20][21]. Further, preexisting systemic disorders were also proved to modify the natural history of COVID-19, usually exacerbating its course and resulting in a more complex presentation of the infection.…”
Section: Introductionmentioning
confidence: 99%